1993
DOI: 10.1063/1.353046
|View full text |Cite
|
Sign up to set email alerts
|

Thomson scattering measurements of electron temperature and density in an electron cyclotron resonance plasma

Abstract: Articles you may be interested inComparative electron temperature measurements of Thomson scattering and electron cyclotron emission diagnostics in TCABR plasmasa) Rev. Sci. Instrum. 81, 10D529 (2010); 10.1063/1.3494379 Measurement of electron temperature and density in an argon microdischarge by laser Thomson scattering Appl.A comparison of spectroscopic and Thomson scattering measurements of electron densities and temperatures in a transient expanding plasma flow Electron temperature T, and density n, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 16 publications
2
49
0
1
Order By: Relevance
“…[14][15][16][17][18][19][20] LTS experiments in microdischarges are challenging because of the low signal and excessive stray light. LTS has been widely used for diagnostics of high temperature, high density plasmas, 12,13 as well as low pressure nonequilibrium discharges.…”
Section: Measurement Of Electron Temperature and Density In An Argon mentioning
confidence: 99%
“…[14][15][16][17][18][19][20] LTS experiments in microdischarges are challenging because of the low signal and excessive stray light. LTS has been widely used for diagnostics of high temperature, high density plasmas, 12,13 as well as low pressure nonequilibrium discharges.…”
Section: Measurement Of Electron Temperature and Density In An Argon mentioning
confidence: 99%
“…2. The Thomson scattering system was arranged in the plane perpendicular to the chamber axis, and is shown schematically in Fig.…”
Section: A Ecr Apparatus and Thomson Scattering Systemmentioning
confidence: 99%
“…Laser Thomson scattering was applied as a diagnostic method for analyzing electron behavior in the ECR plasma. In previous Thomson scattering experiments, 2 it was shown that the signal-to-noise ratio that can be obtained is sufficient to measure electron densities down to less than 10 17 m Ϫ3 , and that the method is nondisturbing to the plasma and unambiguous in the interpretation of the results, compared with electric probe methods. 3 A new laser Thomson scattering system that has enabled spatial profiles of the electron density and temperature to be measured was constructed.…”
Section: Introductionmentioning
confidence: 99%
“…TS is employed to determine the electron density n e and temperature T e with good spatial resolution [8][9][10][11][12][13][14][15]. Rayleigh scattering gives us spatially resolved heavy particle temperature T g [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%